Unique fractional calculus engineering laboratory for learning and research. Issue 1 (January 2020) - Khubalkar, Swapnil; Junghare, Anjali; Aware, Mohan; Das, Shantanu
In this paper, a novel prototype laboratory is presented for engineering education, in which experiments are based on the fractional calculus. The prototypes of analog and digital fractional-order proportional-integral-derivative (PID) controllers are built in the laboratory. These fractional-order PID controllers are applied to linear and nonlinear plants to demonstrate the effectiveness of fractional-order calculus in real time. These experiments are designed, developed, and implemented on the analog and digital platforms. These controllers are integrated to control the DC motor, brushless DC motor, and magnetic levitation modules through hardware-in-loop as well as stand-alone systems. The analog type of fractional-order PID implementation is carried out by using passive components (i.e. resistances and capacitances) with an operational amplifier. However, real-time digital implementation is carried out using field-programmable gate array and digital signal processor. This paper describes how the experiments on fractional calculus can be tailored for graduate, undergraduate students' education and extended for research in this emerging area.